Food in a colonial setting: The faunal assemblage of a short-lived Seleucid-founded site in the Near East. (October 2022) - Pines, Miriam; Mienis, Henk; Rittner, Oz; Lichtenberger, Achim; Tal, Oren
Highlights: Studying animal bones and mollusks enhances our understanding of ancient eating habits. This study presents the diet and eating habits of Hellenic settlers in the southern Levant. Consumption of snails and pork are more akin to central Mediterranean rather than the Levant. Abstract: In this paper we present the analysis of faunal ecofacts retrieved from well-secured features during recent excavation work carried out in 2019 and 2020 by the German-Israeli Tell Iẓṭabba Excavation Project in the Seleucid-founded town of Nysa-Scythopolis. Founded under Antiochus IV Epiphanes (175–164 BCE) and destroyed by the Hasmonaeans in the later years of John Hyrcanus (in 107 BCE). The site offers a unique opportunity for observing the dietary habits of its Foreign Hellenistic settlers: the well-secured Seleucid assemblages, together with their varied provenance, offer new information on the Hellenistic southern Levant via a unique case-study employing high-resolution systematic analysis. The faunal assemblage from Tell Iẓṭabba (Nysa) provides a clearer picture of dietary practices in Hellenistic Palestine, focusing on the settlers at the site. By presenting the consumption patterns, based on animal bones and mollusks unearthed from the site's layer of Hellenistic occupation, we offer a comprehensive overview of the meat sources of food at the site and present a distinct cultural practice which is markable different from regional Levantine dietary customs.